Hubungan Faktor Risiko dengan Keberhasilan Asi Eksklusif dalam Pendekatan Biopsikososial - badri, Putri rizki; Kesuma, Putri Zalika Laila Mardiah; Alfarizi, Ahmad Bayu; Asmalia, Resy; Urfi, Aiverda (Syifa'Medika, 2025)
Exclusive breastfeeding is breast milk (EBF) given to babies from 0-6 months of age without any additional food, including water. The goal is for babies to achieve optimal growth, development and health because breast milk contains complete nutrition for babies. Several factors that can influence breastfeeding are biological, psychological and social factors for breastfeeding mothers. This study aimed to determine the relationship between the biopsychosocial model and exclusive breastfeeding in Posyandu, Kelurahan 16 Ulu. This type of research was descriptive analytic with a cross sectional design, used primary data with a sample size of 64 people taken by purposive sampling. The results obtained were obtained from three factors, namely biopsychosocial, only educational variables from social factors related to exclusive breastfeeding. The statistical test results obtained a p value > 0.05 for all variables except education. So it can be concluded that there is a relationship between education and exclusive breastfeeding at Posyandu, Kelurahan 16 Ulu.